Macrophages-derived Factor XIII links coagulation to inflammation in COPD - Bazzan, Erica; Casara, Alvise; Radu, Claudia Maria; Tinè, Mariaenrica; Biondini, Davide; Faccioli, Eleonora; Pezzuto, Federica; Bernardinello, Nicol; Conti, Maria; Balestro, Elisabetta; Calabrese, Fiorella; Simioni, Paolo; et al. (Frontiers in Immunology, 2023)
Abstract Background. The local, extravascular, activation of the coagulation system in response to injury is a key factor mediating the resulting inflammatory response. Coagulation Factor XIIIA (FXIIIA) found in alveolar macrophages (AM) and dendritic cells (DC), by influencing fibrin stability, might be an inflammatory modifier in COPD. Aims. To study the expression of FXIIIA in AM and Langerin+DC (DC-1) and their relation to the inflammatory response and disease progression in COPD. Methods. In 47 surgical lungs, 36 from smokers (22 COPD and 14 no-COPD) and 11 from non-smokers we quantified by immunohistochemistry FXIIIA expression in AM and DC-1 along with numbers of CD8+Tcells and CXCR3 expression in lung parenchyma and airways. Lung function was measured prior to surgery. Results. The percentage of AM expressing FXIII (%FXIII+AM) was higher in COPD than no-COPD and non-smokers. DC-1 expressed FXIIIA and their numbers were higher in COPD than no-COPD and non-smokers. DC-1 positively correlated with %FXIII+AM (r=0.43; p<0.018). CD8+Tcells, which were higher in COPD than in no-COPD, were correlated with DC-1 (p<0.01) and %FXIII+AM. CXCR3+ cells were increased in COPD and correlated with %FXIII+AM (p<0.05). Both %FXIII+AM (r=-0.6; p=0.001) and DC-1 (r=-0.7; p=0.001) correlated inversely with FEV1/FVC. Conclusions. FXIIIA, an important link between the extravascular coagulation cascade and inflammatory response, is significantly expressed in alveolar macrophages and dendritic cells of smokers with COPD, suggesting that it could play an important role in the adaptive inflammatory reaction characteristic of the disease.